ATP Hydrolysis and Synthesis of a Rotary Motor V-ATPase from Thermus thermophilus - Nakano, Masahiro (American Society for Biochemistry and Molecular Biology, 2008)
Vacuolar-type H(+)-ATPase (V-ATPase) catalyzes ATP synthesis and hydrolysis coupled with proton translocation across membranes via a rotary motor mechanism. Here we report biochemical and biophysical catalytic properties of V-ATPase from Thermus thermophilus. ATP hydrolysis of V-ATPase was severely inhibited by entrapment of Mg-ADP in the catalytic site. In contrast, the enzyme was very active for ATP synthesis (∼70 s(–1)) with the K(m) values for ADP and phosphate being 4.7 ± 0.5 and 460 ± 30 μm, respectively. Single molecule observation showed V-ATPase rotated in a 120° stepwise manner, and analysis of dwelling time allowed the binding rate constant k(on) for ATP to be estimated (∼1.1 × 10(6) m(–1) s(–1)), which was much lower than the k(on) (= V(max)/K(m)) for ADP (∼1.4 × 10(7) m(–1) s(–1)). The slower [Formula: see text] than [Formula: see text] and strong Mg-ADP inhibition may contribute to prevent wasteful consumption of ATP under in vivo conditions when the proton motive force collapses.